National Evaluation of Prison Industry Enhancement Certification Program (PIECP), 1996-2003 (United States) - Smith, Cindy J. ([Verlag nicht ermittelbar], 2009)
The goal of this study was to conduct a national empirical assessment of post-release employment and recidivism effects based on legislative intent for inmates participating in Prison Industries Enhancement Certification Program (PIECP) as compared to participants in traditional industries (TI) and those involved in other than work (OTW) activities. The research design for this study was a quasi-experimental design using matched samples. The inmates were matched using six criteria. Exact matches were made on race, gender, crime type, and category matches on age, time served, and number of disciplinary reports. A cluster sampling strategy was used for site selection. This strategy resulted in a selection of five states which were not identified in the study. The researchers then collected data on 6,464 individuals by completing record reviews of outcomes for the 3 matched samples, each of approximately 2,200 inmates released from 46 prisons across 5 PIECP states between January 1, 1996, and June 30, 2001. Variables include demographic information, time incarcerated, number of disciplinary reports, crime type, number of major disciplinary reports reviewed, group type, number of quarters from release to employment, censored variables, number of quarters from employed to job loss, time from release variables, number of possible follow-up quarters, proportion of follow-up time worked, wage variables, number of quarters worked variables, no work ever, and cluster number of case.